A68 Inhalation of traffic-related air pollution using personal monitoring and wearable technology. Issue 2 (June 2015) - Dons, Evi; Laeremans, Michelle; Avila-Palencia, Ione; Pablo Orjuela, Juan; Cole-Hunter, Thomas; Louwies, Tijs; De Boever, Patrick; de Nazelle, Audrey; Nieuwenhuijsen, Mark; Int Panis, Luc
Abstract: Background: Many studies indicate that air pollution can lead to both acute and chronic health effects. From a husband/wife study (Dons et al., Atmos Environ, 2011), we know that the time-activity pattern is important in determining exposure to air pollution with a difference of up to 30% in exposure between partners. Exposure in the transport microenvironment contributed 20% to cumulative exposure; whereas only 6% of the time is spent travelling. Moreover, when accounting for breathing rates, time in transport can contribute up to a third of the total inhaled particles. Until now, estimation of inhaled concentration is usually based upon literature values or on cumbersome rather than convenient wearable personal health monitors. Methods: A personal monitoring study on 40 test persons in Antwerp (Belgium) was set up measuring black carbon (BC), time-activity patterns, geo-location, and physical activity through accelerometry (ExpoApp) and health markers. Activity types and transport modes were annotated based on GPS, accelerometry and physical activity data. Several sensors that register energy expenditure and cardiovascular function (Sensewear armband, Zephyr BioHarness) are being applied for seven consecutive days on these volunteers while inhalation of BC is calculated. Four different methods to calculate minute ventilation where applied: (1) based on activity classification and minute ventilation estimates from literature; (2) based on heart rates; (3) based on breathing rates; (4) based on METs – metabolic equivalents of work, energy expenditure, and oxygen consumption. Currently a larger multicentre study is ongoing within the framework of the European FP7 PASTA project, including Barcelona and London. Results: Initial results based on the activity classification provided by the Sensewear Armband, show that volunteers (all office workers) were sleeping for 28% of the time, and at rest for 58% of the time. Volunteers were travelling for 8% of the day. Seven-day average exposure to BC was 1142 ±165 ng/m³. Average daily inhaled BC concentrations accumulated close to 20 µg; depending on the calculation method, inhaled concentrations differed considerably (14±7%), with method (1) giving the highest values. Only while sleeping, the estimation method does not seem to influence the results. Conclusions: Especially for traffic-related air pollution, exposure away from home (while travelling and in other non-home microenvironments) is a significant confounder in exposure assessment. In future epidemiological studies it is key to estimate personal exposure and inhaled dose rather than concentrations on fixed locations; using mobile sensors and wearables this comes within reach.